DAMPAK BEBAN KERJA TERHADAP CYBERLOAFING YANG DIMODERASI OLEH STRES KERJA PADA KARYAWAN GEN Z DI ERA DIGITAL - Yunita, Putu Irma; Pradhana, Putu Darmawan; Mertha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.06.TAHUN.2025DO - 10.24843/EEB.2025.v14.i06.p05, 2025)
Cyberloafing, a counterproductive work behavior, often occurs in today's work world. This is triggered by the increasingly massive internet use in the digital era. In addition, Gen Z, which is the largest workforce today, is very familiar with the internet and has the potential to commit cyberloafing. This study examines the relationship between workload, work stress, and cyberloafing behavior in the Generation Z workforce in the technology era. The psychological impact, namely work stress, is a mediating variable in this study. Survey data was obtained by distributing it via Google Forms to 126 Gen Z employees in Bali. Partial Least Squares Analysis, Variance-Based Structural Equation Modeling, was used to verify the research model. The study's results showed that work stress significantly affected cyberloafing behavior. Interestingly, the workload does not encourage Gen Z employees to do cyberloafing. In addition, work stress can also moderate the effect of workload on cyberloafing behavior. The results of this study can provide considerations for managers in forming regulations related to internet use in the workplace. Paying attention to employee mental health can provide optimal contribution to the company.